ALD Pt nanoparticles and thin-film coatings enhancing the stability and performance of silicon photocathodes for solar water splitting. Issue 12 (21st May 2021) - Trompoukis, Christos; Feng, Ji-Yu; Bosserez, Tom; Rongé, Jan; Dendooven, Jolien; Detavernier, Christophe; Baets, Roel; Martens, Johan A.
Abstract : ALD is used to deposit Pt nanoparticles capped by ultra-thin SiO2 layers of various thicknesses to enhance the performance and stability of Si photocathodes used for solar water splitting. Enhanced stability is achieved compared to the reference case. Abstract : We report on thin-film coatings and catalyst nanoparticles both deposited by atomic layer deposition (ALD) on silicon (Si) photocathodes that simultaneously enhance their performance and stability. Regarding thin-film coatings, we scan various materials (SiO2, TiO2 and Al2 O3 ) appropriate for the electrical passivation of Si surface defects, which result in high minority carrier lifetimes (up to 100 μs). However, these passivating layers seem to act as a barrier for the photogenerated carriers obstructing them from participating in the hydrogen evolution reaction, thus limiting the onset potential ( V on ). Regarding platinum (Pt) nanoparticles, two deposition approaches are followed based on using different co-reactants during the ALD process, i.e. an O2 pulse or a N2 -plasma pulse, with the latter resulting in a higher V on (505 mV). By combining thin-film SiO2 coatings of various thicknesses deposited on top of ALD Pt nanoparticles, a synergetic effect of performance and stability enhancement is observed, with V on values reaching 525 mV. Finally, by systematically studying the Si photocathodes in a day/night cycle operation and using the case of electroless deposited Pt nanoparticles as a benchmark, the N2 -plasma deposited Pt nanoparticles coated by ultra-thin SiO2 film show an enhanced stability (85 h-4 days/night cycles).